ANALISIS KEPUTUSAN NASABAH MENABUNG DI BANK SYARIAH (STUDI KASUS DI PT. BPRS PUDUARTA INSANI) - Nurul Inayah; Sri Sudiarti (Universitas Islam Negeri Sumatera Utara, 2017)
The research was aimed to analyze the customer’s saving decision at sharia bank (a case study in PT. BPRS Puduarta Insani). The method used in this research is a quantitative approach by multiple linear regression analysis, it was supported by stationarity test and the classical assumption test in Eviews version 8.0. The results showed that in the partially test the customer’s knowledge had a positive and significant influence on the saving decision amounted to 35,2% and this is the most dominant factor, bank characteristics had a positive and significant influence on the saving decision amounted to 21,8%, service quality had a positive and significant influence on the saving decision amounted to 33,7% and physical object of the bank had a positive and significant influence on the saving decision amounted to 19,9%. And in the simultaneously test the customer’s knowledge, bank characteristics, service quality and physical object of the bank had the significant influence on the saving decision amounted to 65,75% and the rest was influenced by other factors not examined in this research.